(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2013)
In this article, the author attempts an archaeology of the conflicts between the industrial cinema and independent cinema models in the period between1908-13. He focuses in particular On the figures Charles Pathé and Georges Méliès and of the firms Pathé Frères and Star Film respectively. The common preconception that Méliès’ fall was due to his having been overtaken aesthetically will be examined. The author will instead seek the reason amongst economic factors and the pitched battle between film production companies (Pathé Frères and Star Film, but also Gaumont, Edison and the others) for control of the nascent market. Questions around the Edison trust, over production and film rentals will be addressed, in addition to Star Film’s activities in the United States with Gaston Méliès. The little-known partnership that Pathé offered Méliès in 1911-13 presents an opportunity to address a final model: that of the independent filmmaker in the very heart of the industry.